Risk Decision-Making by Head Departments in University of Karbala - Zaid, Zahra Amir Abed (International Journal of Psychosocial Rehabilitation, 2020)
This research has been carried out in the university and aims to, to know the risk level in Decision-Making by head department and to know the difference of statistical significance in the risk level for Decision-making according to the gender change(male-female) and specialization (scientific- human), By using the analyzed and descripted research as being fit with the nature of the current research, the researcher relied. The current research society contains of head departments in the university of Karbala with (42) head departments. And the research sample reached to (42) head department, due the small size society which the researcher has chosen to represents the research sample. The researcher used the risk scale in decision-making which prepared by (Ali, 1995) and contained of (14) stance to achieve her research aims and to pick up the results of the statistic group for social sciences used (spss). And post data analyzing, the currents research concludes to the following results: Head departments in Karbala university are benefitted of low risk level in decision-making. There is no difference of statistical significance in taking decision according to the gender change (Female- male) and specialization (scientific- human). Under the light of these results, a batch of recommendations and suggestions with significance to the research change, have been submitted.